Academic procrastination measurement: Psychometric analysis of a brief version as an ECAD - Chirio-Aldazabal, Diego (2023)
The study had the objective of analyzing the psychometric properties of the Brief Academic Procrastination Scale (EBPA-16). The sample was non-probabilistic and intentional, represented by 478 university students (59.8% women and 40.2% men) from Lima Sur, aged between 18 and 33 years. The study was of the instrumental type, where the EBPA-16 was constructed and applied, made up of 16 items distributed in two dimensions, with a Lickert-type response scale with 5 response options. The results demonstrated the presence of content validity due to Aiken’s V values greater than .80. Homogeneity indices were found in the items (ritc >.20) and multicollinearity was rejected (ritc <.95). For the analysis of the validity based on the internal structure, the existence of a two-dimensional model was demonstrated by means of the AFE with a Pearson correlation matrix and a dimensionality by parallel analysis, which demonstrated a VEA of 38.2% and factor loadings greater than . 30 represented parsimoniously in both factors. Reliability was high due to estimator values greater than .70. The existence of adequate evidence for the validity and reliability of the EBPA-16 was concluded.